"After my husband's circumcision, I know that I am safe from diseases": women's attitudes and risk perceptions towards male circumcision in Iringa, Tanzania. - Erica H Layer (PLoS ONE, 2013)
While male circumcision reduces the risk of female-to-male HIV transmission and certain sexually transmitted infections (STIs), there is little evidence that circumcision provides women with direct protection against HIV. This study used qualitative methods to assess women's perceptions of male circumcision in Iringa, Tanzania. Women in this study had strong preferences for circumcised men because of the low risk perception of HIV with circumcised men, social norms favoring circumcised men, and perceived increased sexual desirability of circumcised men. The health benefits of male circumcision were generally overstated; many respondents falsely believed that women are also directly protected against HIV and that the risk of all STIs is greatly reduced or eliminated in circumcised men. Efforts to engage women about the risks and limitations of male circumcision, in addition to the benefits, should be expanded so that women can accurately assess their risk of HIV or STIs during sexual intercourse with circumcised men.